Does donor‐recipient age difference matter in outcome of heart transplantation?. Issue 7 (19th June 2019) - Ram, Eilon; Lavee, Jacob; Kogan, Alexander; Kassif, Yigal; Elian, Dan; Freimark, Dov; Peled, Yael
Abstract: Objective: Potential interactions between donor‐recipient age difference and outcomes after heart transplantation are not well known. We thus aimed to study the impact of donor‐recipient age difference on heart transplantation outcomes. Methods: Between 1995 and 2017, we assessed 234 heart transplantation patients. Based on donor‐recipient age difference histogram, we stratified these patients into three groups: older donors (donor‐recipient difference > 0; n = 48), younger donors (donor‐recipient difference 0 to −20 years; n = 82), and much younger donors (donor‐recipient difference <−20 years; n = 104). Results: The baseline metabolic risk profile of the recipients was significantly higher for the much younger donor group compared with the younger and older groups, including hypertension (52% vs 33% vs 25%, P  = 0.002), dyslipidemia (51% vs 51% vs 29%, P  = 0.027), diabetes (30% vs 16% vs 17%, P  = 0.044), and smoking history (53% vs 46% vs 29%, P  = 0.024), respectively. There were no significant differences between the groups in long‐term survival, cardiac allograft vasculopathy, or rejection‐free survival in unadjusted and adjusted analyses. In the much younger donor group, gender matching was associated with a lower incidence of primary graft dysfunction (37% vs 58% P  = 0.05). Conclusions: Donor‐recipient age difference does not significantly impact long‐term heart transplantation outcomes.